Development and validation of willingness to communicate, language use and motivation questionnaires - Ubaid, Ullah; Joseph, Ramanair; Soubakeavathi, Rethinasamy (Unimas Publisher, 2021)
The main goal of modern second language (L2) pedagogy is to engender appropriate communication skills among its learners. Hence, willingness to communicate (WTC) in L2 emerged as an important variable in recent years. Several factors have been found to influence students’ L2 WTC directly or indirectly. For this purpose, many scales and questionnaires have been developed so far to examine the factors influencing WTC among L2 students. However, a comprehensive questionnaire on WTC inside ESL classroom is still lacking. Likewise, WTC in relation to language use and motivational orientations in a single study has yet to be investigated. Thus, this study was aimed to develop and validate questionnaires on WTC, language use and motivational orientations. For this purpose, a five-phase model was used. After an extensive literature review, questionnaires on WTC, language use and motivational orientations were framed. Operational definitions of the three constructs were established and the items of the questionnaires were finalised. Two experts in the field of applied linguistics determined the content validity of the questionnaires. At the end, the questionnaires were piloted on 50 undergraduates and 10 ESL teachers. The results revealed that all the instruments were valid and highly reliable.